Memorandum of understanding between Universiti Teknologi MARA and Afridat UG (Haftungsbeschrankt) Germany / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on cooperation, collaboration, academic and scientific thought in respect of providing solutions in renewable energy sectors and commercialization of research results.